Information driven care pathways and procedures - Dickinson,RJ; Kitney,RI (Ifmbe Proceedings, 2014)
The paper addresses the issue of the implementation of care pathways in electronic form. Within the National Health Service (NHS) of England, Care Pathways are becoming increasingly important. These are typically provided by the Department of Health. The Pathways provided are in the form of paper-based schema. They either have to be implemented via paper forms or, as presented here, in electronic form. In addition, care pathways must be seen in the context of the TModel of health care which comprises the care continuum and the biological continuum. The two care pathways which had been chosen as exemplars are myocardial infarction and stroke. However, the objective of the paper is not to discuss the specific care pathways in detail, but, rather, to describe technology which has been developed for their electronic implementation. The result of this implementation is that all the data and information acquired from the implementation of the care pathway is stored in a single clinical information system (CIS), which has incorporated in it the SQL database. Another important element of the system which has been developed is the ability to display data and information in terms of two dashboards (i.e. single screens which show the most important information). The two dashboards display clinical information (the point of care dashboard) and management information (the management dashboard). © Springer International Publishing Switzerland 2014.